Identification of Main Oyster Species and Comparison of Their Genetic Diversity in Zhejiang Coast, South of Yangtze River Estuary - Liu, Sheng; Xue, Qinggang; Xu, Hongqiang; Lin, Zhihua (Frontiers in Marine Science, 2021)
Oysters are an important aquaculture species distributed worldwide, including in Zhejiang Province, located on the east coast of China. Because of the high diversity and complicated introduction history of oysters and their seedlings, there has been much disagreement regarding the origin of each species, and the dominant and indigenous species remain unclear. We sampled 16 batches of oysters from seven sites in three aquaculture bays and found two main oyster species, Crassostrea sikamea and Crassostrea angulata. The former occupied the higher intertidal zone and comprised more than 70% of the cultured oysters. Based on the cytochrome oxidase C subunit I (COI) and mitochondrial noncoding region (MNR), C. sikamea showed higher genetic diversity than C. angulata. The analysis of molecular variance among COI sequences of these species from the Xiangshan Bay populations were comparable to those of other populations and showed that most of the molecular variance was within groups, which was consistent with the low pairwise fixation index FST values. The neutrality test revealed that C. sikamea experienced population expansion events, whereas for C. angulata, the significant Fu’s Fs and non-significant Tajima’s D test results may indicate a possible population expansion event, implying that C. sikamea is likely an indigenous species. The method established based on internal transcribed spacer 1 digestion by the HindIII restriction enzyme is useful for identifying C. sikamea and C. angulata in the local region. The specific primers on the MNR sequence show potential for distinguishing C. sikamea from four other important Crassostrea oysters. These results highlight the abundance of C. sikamea on the Zhejiang coast and lay the foundation for protecting and utilizing the local oyster germplasm resources and for the sustainable development of the oyster industry.